Correlation of Prostaglandin D2 with disease severity of adult asthma - Al-Karkhy, Mohammad A.; Nema, Mustafa; Abdullah, Shatha F. (Journal of the Faculty of Medicine Baghdad, 2020)
Background: Prostaglandin D2 (PGD2) is a lipid mediator appeared as a powerful activator that regulates the T-helper2 (TH2) and Type-2 innate lymphoid cells (ILC2), and functions as diagnostic marker and it has probable therapeutic targets for asthma. Objectives: To define the role of Prostaglandin D2 biomarkers in disease severity, and to forecast disease risk and progression. Patients and methods: A case control study was conducted on Forty four Iraqi asthmatic patients and 44 apparently healthy controls who were age and sex matched. Four ml of blood samples was taken from the study groups for the detection PGD2 using ELISA. Results: The serum level of PGD2 was almost convergent between cases and control group (median= 36.5pg/ml and 35.1 pg/ml respectively). The high median serum concentration of PGD2 showed a strong statistically significant association with the severity of asthmatic patients (39.8 pg/ml) in severe cases compared to (30.84 pg/ml) in moderate cases (P value =0.005). The median concentration of serum PGD2 revealed a higher level in abnormal eosinophil, monocytes and total IgE (42 pg/ml), (48.9 pg/ml) and (38.5 pg/ml) respectively than the median concentration of normal counts. Conclusions: Measuring serum PGD2 in asthmatics is crucial to predict disease susceptibility, severity and disease control.